A Quarter Century of Liver Transplantation: Learning from Livers - Paul C. Adams (Canadian Journal of Gastroenterology)
Liver transplantation has emerged as a powerful tool to increase the understanding of physiological and pathophysiological processes in the liver. Transplantation for metabolic diseases with resolution of the disease process has been the ultimate proof of the hepatic source of the defect. Recurrence of the primary disease in the liver following transplantation has furthered understanding of the pathogenesis of hepatitis and the cell biology of hepatobiliary tumours. The role of genetics and immune factors in the pathogenesis of alcoholic I iver disease may be clarified with the increasing numbers of patients transplanted for alcoholic cirrhosis. Normal gallbladder motility in the denervated transplanted liver questions the role of neuronal influences on gallbladder function. Finally, experimental liver transplantation in animals has been used as a tool to study metabolic problems.